The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1152/ajprenal.00540.2019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sex, androgens, and prostate size on C57BL/6J mouse urinary physiology: urethral histology

Abstract: The National Institutes of Health leveled new focus on sex as a biological variable with the goal of understanding sex-specific differences in health and physiology. We previously published a functional assessment of the impact of sex, androgens, and prostate size on C57BL/6J mouse urinary physiology (Ruetten H, Wegner KA, Zhang HL, Wang P, Sandhu J, Sandhu S, Mueller B, Wang Z, Macoska J, Peterson RE, Bjorling DE, Ricke WA, Marker PC, Vezina CM. Am J Physiol Renal Physiol 317: F996–F1009, 2019). Here, we meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Then, the mice were administered drugs by intravesical instillation once a week for a total of four times, during which the mice urinated normally since the diameter of urethras of mice (≈2 mm) was greater than the diameter of BSA 20 ‐MBs. [ 27 ] To visually monitor the progress of bladder tumors, noninvasive ultrasound imaging was used to image the tumors throughout the whole treatment process. As shown in Figure 6b, there was a hyperechoic signal in the bladder at day 0, indicating that the orthotopic tumors were successfully constructed, in which the size of tumors could not be identical because of the individual differences between mice.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the mice were administered drugs by intravesical instillation once a week for a total of four times, during which the mice urinated normally since the diameter of urethras of mice (≈2 mm) was greater than the diameter of BSA 20 ‐MBs. [ 27 ] To visually monitor the progress of bladder tumors, noninvasive ultrasound imaging was used to image the tumors throughout the whole treatment process. As shown in Figure 6b, there was a hyperechoic signal in the bladder at day 0, indicating that the orthotopic tumors were successfully constructed, in which the size of tumors could not be identical because of the individual differences between mice.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of previous basic research investigations on the mechanisms of LUTD after spinal cord injury (SCI) were predominantly performed using female rodents 3–5 . In addition, there have been no studies of bladder and urethral coordination in male mice although several researchers have suggested that there are sex differences in the urethra, in terms of its function, morphology, and distribution of receptors such as α1‐adrenoceptors and hormonal receptors 6–8 . It has been shown that male and female rats exhibit bursting activity of the external urethral sphincter (EUS) during voiding, which acts as urethral pumping function to help efficient voiding 9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In addition, there have been no studies of bladder and urethral coordination in male mice although several researchers have suggested that there are sex differences in the urethra, in terms of its function, morphology, and distribution of receptors such as α1adrenoceptors and hormonal receptors. [6][7][8] It has been shown that male and female rats exhibit bursting activity of the external urethral sphincter (EUS) during voiding, which acts as urethral pumping function to help efficient voiding. [9][10][11] In contrast, in humans 12 and in female mice, EUS relaxes during voiding, so that voiding occurs during EUSelectromyography (EMG) silent periods in both spinal intact (SI) and SCI conditions, 10 although it is not well clarified whether EUS bursting activity is involved in efficient voiding in male mice.…”
Section: Introductionmentioning
confidence: 99%